Effects of quercetin on antioxidant potential in the experimental periodontitis development - Demkovych, Andrii (Interv Med Appl Sci, 2019)
The results of experimental research of antioxidant system are presented in this article. Superoxide dismutase activity, catalase, and ceruloplasmin have been determined on the 7(th) and 14(th) days of experimental periodontitis development both without correction and with the injection of a water-soluble quercetin drug (corvitin). Hence, there was a decrease in superoxide dismutase activity, intensive increase in catalase activity, and ceruloplasmin maintenance in the blood serum during acute period of inflammatory process. The usage of flavonoid for 7  days resulted in stabilization of radical oxidation due to reduction of superoxide dismutase activity, maintenance at the high-level catalase activity, and ceruloplasmin concentration in the rat’s blood plasma with experimental bacterial-immune periodontitis.